Limited social support is associated with depression, anxiety, and insomnia in a Japanese working population - Omichi, Chie; Kaminishi, Yuki; Kadotani, Hiroshi; Sumi, Yukiyoshi; Ubara, Ayaka; Nishikawa, Kohei; Matsuda, Arichika; Ozeki, Yuji (Frontiers in Public Health, 2022)
Background: Lack of social support is associated with depression, anxiety, and insomnia. This study aimed to determine the source of support related to depression, anxiety, and insomnia among Japanese workers. Methods: As part of a cohort study, we conducted a questionnaire survey among city government employees in Koka City, Shiga Prefecture, Japan, from September 2021 to March 2022. We used the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder -7 (GAD-7), and Insomnia Severity Index (ISI) to assess depressive symptoms, anxiety symptoms, and insomnia, respectively. We used the Brief Job Stress Questionnaire (BJSQ) to assess job stressors and social support (from supervisors, colleagues, and family). Results: A total of 1852 Japanese employees (38.4% male, 45.9±12.9 years) participated in the survey, with 15.5%, 10.8%, and 8.2% of the participants having depressive symptoms (PHQ-9 ≥ 10), anxiety symptoms (GAD-7 ≥ 10), and insomnia (ISI ≥ 15), respectively. The logistic regression analysis suggested that job stressors were associated with depressive symptoms (p<0.001), anxiety symptoms (p<0.001), and insomnia (p=0.008). In contrast, support from co-workers (p=0.001) and family members (p<0.001) was associated with decreased depressive symptoms. Support from family members was associated with decreased insomnia (P =0.005). Conclusion: Social support from co-workers and family may be associated with reduced depressive symptoms, and family support may be associated with reduced insomnia in the Japanese working population.